Oxygen delivery during extreme anemia with ultra-pure earthworm hemoglobin - Elmer, Jacob (2012)
AIM: Lumbricus terrestris (earthworm) erythrocruorin (LtEc) is a naturally occurring extracellular hemoglobin (Hb) with high molecular weight (3.6 MDa), low autoxidation rate, and limited nitric oxide (NO) dioxygenation activity. These properties make LtEc an potential candidate for use as red blood cell (RBC) substitute, i.e. Hb-based oxygen carrier (HBOC). Previous studies have shown that small amounts of LtEc can be safely transfused into mice, rats, and hamsters without eliciting major side-effects. Therefore, this study was designed to understand oxygen (O(2)) transports to tissues and systemic/microvascular hemodynamics by LtEc during anemic conditions. MAIN METHODS: Hamsters fitted with dorsal window chambers were hemodiluted to 18% hematocrit (Hct) using 6 g/dL dextran 70 kDa (Dex70). Hemodilution was then continued to 11% Hct using 10 g/dL LtEc, 6 g/dL Dex70 or 10 g/dL human serum albumin (HSA). Blood pressure, heart rate, blood gas parameters, and microvascular hemodynamics, microvascular blood flow, functional capillary density (FCD), intravascular pO(2) and perivascular pO(2) were studied. KEY FINDINGS: LtEc maintained blood pressure without inducing vasoconstriction, while increasing microvascular perfusion and FCD relative to Dex70 and HSA. LtEc increased blood O(2) carrying capacity, maintained systemic and microvascular parameters without decreasing arteriolar diameter or increasing vascular resistance with during extreme anemia. LtEc transfusion effects in blood flow and O(2) carrying capacity increased O(2) delivery compared to conventional plasma expanders. SIGNIFICANCE: LtEc or synthetic molecules that replicate the characteristics of LtEc, could be an effective O(2) carrier with potential to be used in transfusion medicine to prevent tissue anoxia resulting from severe anemia.